2001
DOI: 10.1016/s0735-1097(00)01188-8
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-methylnorepinephrine, a selective alpha2-adrenergic agonist for cardiac resuscitation

Abstract: The selective alpha2-adrenergic agonist, alphaMNE, was as effective as epinephrine for initial cardiac resuscitation but provided strikingly better postresuscitation myocardial function and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 22 publications
2
28
0
1
Order By: Relevance
“…32 Experimental studies by our group with the selective ␣ 2 -agonist ␣-methylnorepinephrine confirmed improved outcomes with fewer postresuscita- tion arrhythmias and less postresuscitation myocardial dysfunction compared with unblocked epinephrine. 33,34 When the ␣ 2 -actions of epinephrine were blocked with yohimbine, the therapeutic benefits of epinephrine for CPR were diminished. 33 The incentive to the present study was therefore to secure the rationale for a selective ␣ 2 -agonist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Experimental studies by our group with the selective ␣ 2 -agonist ␣-methylnorepinephrine confirmed improved outcomes with fewer postresuscita- tion arrhythmias and less postresuscitation myocardial dysfunction compared with unblocked epinephrine. 33,34 When the ␣ 2 -actions of epinephrine were blocked with yohimbine, the therapeutic benefits of epinephrine for CPR were diminished. 33 The incentive to the present study was therefore to secure the rationale for a selective ␣ 2 -agonist.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 When the ␣ 2 -actions of epinephrine were blocked with yohimbine, the therapeutic benefits of epinephrine for CPR were diminished. 33 The incentive to the present study was therefore to secure the rationale for a selective ␣ 2 -agonist.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenoceptors of the α1 subtype are particularly prone to desensitisation during cardiac arrest (Sun et al 2001), and, together with the potentially deleterious effects of α-adrenoceptor activation during resuscitation, this has been used as an argument for the use of selective α2-adrenoceptor agonists for resuscitation (Sun et al 2001).…”
Section: Adrenoceptor Desensitisationmentioning
confidence: 99%
“…The argument given is that activation of β-adrenoceptors is detrimental in resuscitation, because they increase the energy requirements of the heart, as do α1-adrenoceptors to a lesser extent. The latter also become rapidly desensitised during ischaemia (Sun et al 2001). Clonidine is unsuitable as it causes a paradoxical fall in blood pressure.…”
Section: Selective α-Adrenoceptor Agonistsmentioning
confidence: 99%
See 1 more Smart Citation